Angiotensin II type 2 receptor prevents extracellular matrix accumulation in human peritoneal mesothelial cell by ameliorating lipid disorder via LOX‐1 suppression. Issue 1 (31st December 2022) - Liu, Jing; Jin, Bo; Lu, Jian; Feng, Yuan; Li, Nan; Wan, Cheng; Zhang, Qing-Yan; Jiang, Chun-Ming
Abstract: Evidence suggests that intracellular angiotensin II type 1 receptor (AT1) contributes to peritoneal fibrosis (PF) under high glucose (HG)-based dialysates. It is generally believed that AT2 antagonisticly affects AT1 function. The aim of this study was to explore whether AT2 activation is beneficial for attenuating human peritoneal mesothelial cell (HPMC) injury due to HG. We treated a HPMC line with HG to induce extracellular matrix (ECM) formation. AT2 was increased and blocked using CGP42112A and AT2 siRNA. Lipid deposition was detected, signaling molecules associated with lectin-like oxidized lipoprotein receptor-1 (LOX-1) and ECM proteins were evaluated by real-time PCR and western blot. The results showed that HG led to AT2 inhibition in HPMCs, inhibition of AT2 further aggravated the expression of ECM proteins, including α-smooth muscle actin, fibroblast specific protein-1 and collagen I, while AT2 decreased the expression of ECM proteins, even during HG stimulation. Interestingly, there was a parallel change in lipid accumulation and ECM formation when AT2 was increased or depressed. Moreover, AT2-mediated decreased ECM production was associated with reduced lipid accumulation in HPMCs and depended on the downregulation of LOX-1. Further analysis showed that HG increased oxidized low-density lipoprotein (ox-LDL) deposition in HPMCs concomitant with an enhanced expression of ECM components, whereas blocking LOX-1 reversed ox-LDL deposition even in the presence of HG. This effect was also accompanied by the remission of ECM accumulation. Our results suggested that AT2 prevented ECM formation in HG-stimulated HPMCs by ameliorating lipid via LOX‐1 suppression.